Synthesis of high purity magnesia MgO from Algerian dolomite ore (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
A nanometric Mg(OH)2 and MgO particles with high purity were successfully synthesized from Algerian dolomite via a leaching-precipitation-calcination process. The effect of leaching parameters such as H2SO4 acid concentration (C), temperature (T), time (t), solid/liquid ratio (S/L), and precipitation parameters: type of precipitating base (KOH, NaOH, NH4OH), OH-/Mg2+ ratio, and temperature on the obtained product properties were investigated using Taguchi approach. The optimal leaching conditions were selected as: C=5M, T=65 °C, t=15 min, and S/L ratio=1:5. Whereas, the potassium hydroxide (KOH) was selected as the optimal precipitating base with OH-/Mg2+ = 10.5. The calcination of the precipitates at 800 °C during 2 h made it possible to produce a high purity MgO (~99.45 %) with a crystallite size of approximately 16.5 nm and particles in the form of agglomerated porous plates with a high SAA (70.42 m2/g) which may be of interest for some applications such as catalysts or supports.
Keywords: Dolomite, Acid leaching, Precipitation, Mg(OH)2, MgO, Calcination